The adoption of green market orientation in logistic industries: Empirical evidence from Vietnamese SMEs - Quang-Huy Ngo (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Recently, the Vietnamese government established an ambitious plan that strongly promotes the development of the logistic industry. However, there is an environmental concern regarding this development. In addition, adopting environmental management practices may reduce the performance of small and medium enterprises (SMEs). Therefore, this study draws upon the natural resource-based and ambidextrous views of green innovation to examine the impact of green market orientation on performance. Particularly, this study proposes that adopting green market orientation permits logistic small and medium enterprises (SMEs) to improve exploitational and exploratory green innovation and, as such, results in the implications of organizational performance based on the balanced scorecard approach. Data were collected from 338 SMEs operating in the logistics industry. Partial least squares structural equation modeling was used to assess the data. The results indicate that the adoption of GMO permits these SMEs to indirectly improve their operational performance through exploitational and exploratory green innovation. These results provide practical implications for managers of logistic SMEs in Vietnam. In addition, this study also contributes to the literature by addressing the gaps in the existing literature.
Keywords: 650; ambidextrous green innovation; green market orientation; logistic providers; organizational performance; SME; Vietnam